Implementation of Public Relations in the Development of Quality Education - Delima; Jibrail Bin Yusuf (Tahta Media Group, 2023)
Progressive steps must be taken immediately to improve the quality of madrasa management. The management hopes a paradigm, approach, and creative change will be realised systematically and continuously in the teacher's mentality. In improving it, it is indeed challenging to apply the techniques of Islamic institutions. However, all efforts to improve the quality of these concepts can have positive implications in the future. To achieve management work goals, create coordination and communicate with representatives in a way that guarantees results, good management requires more practice in relationship management. Implementing madrasah-based management (MBM) to improve the quality of Islamic education is necessary and must be implemented immediately. MBM has madrasah autonomy in determining decision-making. MBM aims to strengthen madrasas. Lastly, madrasas can improve the abilities of all madrasah residents so that madrasas can take the initiative and innovate to improve the quality of learning in madrasah.